Development of a cell-free and growth factor-free hydrogel capable of inducing angiogenesis and innervation after subcutaneous implantation. (November 2019) - dos Santos, Bruno Paiva; Garbay, Bertrand; Fenelon, Mathilde; Rosselin, Marie; Garanger, Elisabeth; Lecommandoux, Sébastien; Oliveira, Hugo; Amédée, Joëlle
Graphical abstract: Abstract: Despite significant progress in the field of biomaterials for bone repair, the lack of attention to the vascular and nervous networks within bone implants could be one of the main reasons for the delayed or impaired recovery of bone defects. The design of innovative biomaterials should improve the host capacity of healing to restore a functional tissue, taking into account that the nerve systems closely interact with blood vessels in the bone tissue. The aim of this work is to develop a cell-free and growth factor-free hydrogel capable to promote angiogenesis and innervation. To this end, we have used elastin-like polypeptides (ELPs), poly(ethylene glycol) (PEG) and increasing concentrations of the adhesion peptide IKVAV (25% (w/w) representing 1.7 mM and 50% (w/w) representing 4.1 mM) to formulate and produce hydrogels. When characterized in vitro, hydrogels have fine-tunable rheological properties, microporous structure and are biocompatible. At the biological level, 50% IKVAV composition up-regulated Runx2, Osx, Spp1, Vegfa and Bmp2 in mesenchymal stromal cells and Tek in endothelial cells, and sustained the formation of long neurites in sensory neurons. When implanted subcutaneously in mice, hydrogels induced no signals of major inflammation and the 50% IKVAV composition induced higher vessel density and formation of nervous terminations in the peripheral tissue. This novel composite has important features for tissue engineering, showing higher osteogenic, angiogenic and innervation potential in vitro, being not inflammatory in vivo, and inducing angiogenesis and innervation subcutaneously. Statement of Significance: One of the main limitations in the field of tissue engineering remains the sufficient vascularization and innervation during tissue repair. In this scope, the development of advanced biomaterials that can support these processes is of crucial importance. Here, we formulated different compositions of Elastin-like polypeptide-based hydrogels bearing the IKVAV adhesion sequence. These compositions showed controlled mechanical properties, and were degradable in vitro . Additionally, we could identify in vitro a composition capable to promote neurite formation and to modulate endothelial and mesenchymal stromal cells gene expression, in view of angiogenesis and osteogenesis, respectively. When tested in vivo, it showed no signs of major inflammation and induced the formation of a highly vascularized and innervated neotissue. In this sense, our approach represents a potential advance in the development of new strategies to promote tissue regeneration, taking into account both angiogenesis and innervation.